SELF-REGULATION AS A FACTOR IN PERSONAL-PROFESSIONAL SELF-DEVELOPMENT OF FUTURE SPECIALISTS - Zhanna G. Garanina; Olga E. Maltseva (National Research Mordova State University, 2016)
Introduction: the article considers the problem of personal and professional self-development of future specialists at the stage of higher education and the role of self-regulation in this process. The specifics and the stage of self-regulation process, among which are stages of awareness of the importance of selfdevelopment process, the formation of personal and professional goals, assessment of possible conditions of its achievement, self-programming stages of performing activities, monitoring and evaluation of the achievement of self-development purposes. Materials and Methods: the author used psychodiagnostic methods aimed at identifying the personal and profes¬sional characteristics of students. The correlation and cluster analysis was used for statistical treatment of results. Results: As a result of experimental research on personal and professional self-development of psychology students the factors were identified, which play an important role in achieving self-development purposes in the course of training. Cluster analysis revealed three groups of students with different levels of development of self-regulation, willingness to self-knowledge and self-development, and the level of self-control and self-efficacy. Discussion and Conclusions: the results show that self-regulation of students is related to such characteristics as commitment to self-development, self-attitude, self-efficacy and reflection. Professional and personal self-development of psychology students is quite a meaningful life value, which depends on the awareness of their professional and personal goals as well as on the level of formation of regulatory and reflective qualities that affect the focus and systematic process of personality .